An introduction to positive economics - Lipsey, Richard G. (London : Weindenfeld and Nicolson, 1971)
This book gives a detailed and valuable survey of the UK economy that is descriptive rather than analytical. There are three major themes of this textbook: an attempt to explain what economic theory is about, an attempt to elaborate within the confines of an introduction to economic theory, the relation between theory and real-world observations, and a consideration of the relation between economic theory and economic policy.
Includes bibliographical references and index.
oif 04/02/2015
Loans
Keywords: Economics